HUBUNGAN KEKUATAN OTOT LENGAN DAN POWER OTOT TUNGKAI DENGAN KECEPATAN RENANG GAYA BEBAS 50 M PORT QUEEN AQUATIC SWIMMING CLUB - Adela Sulastri, Aprilia; Alpian; Irpan Abdurahman; Debi Krisna Irawan; Iqbal Fajarullah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the relationship between arm muscle strength and leg muscle power with 50M freestyle swimming speed of swimming club members at Port Queen Aquatic Swimming Club. Data normality tests showed that all variables were normally distributed. The research method used was a quantitative method with a correlational approach. The instruments used included a push-up test to measure arm muscle strength, a vertical jump test to measure leg muscle power, and a 50-meter freestyle swimming test to measure swimming speed. Data analysis used the Pearson Product Moment correlation test and multiple linear regression with a significance level of 0.05. The results of the study showed that: (1) there is a significant relationship between arm muscle strength and 50-meter freestyle swimming speed with a correlation coefficient value of r = -0.629 and a significance of 0.001 (p < 0.05); (2) there is a significant relationship between leg muscle power and 50-meter freestyle swimming speed with a correlation coefficient value of r = -0.732 and a significance of 0.000 (p < 0.05); and (3) there is a significant relationship simultaneously between arm muscle strength and leg muscle power and 50-meter freestyle swimming speed with a value of R = 0.765, R Square = 0.585, and F = 14.082 with a significance of 0.000 (p < 0.05). These results indicate that 58.5% of the variation in 50-meter freestyle swimming speed can be explained by arm muscle strength and leg muscle power, while 41.5% is influenced by other factors outside the study. Thus, arm muscle strength and leg muscle power are components of physical condition that play a crucial role in increasing speed in the 50-meter freestyle.